ЕНЕРГОЕФЕКТИВНА СИСТЕМА КЕРУВАННЯ ЕЛЕКТРОТЕХНОЛОГІЧНИМ КОМПЛЕКСОМ ПРОМИСЛОВИХ ТЕПЛИЦЬ - Лисенко, В.П.; Болбот, І.М.; Лендєл , Т.І. (Інститут електродинаміки НАН України, Київ, 2019)
Developed energy efficient system of electrotechnological complex control in industrial greenhouse. Assessment of quality of plant products based on the use of desirability functions Harrington. This allows to define the parameters of the microclimate (temperature plants, temperature and humidity), profit maximizing production. Developed mobile robot that is able to move through the greenhouse. The mobile robotic performs measurements of the main microclimate parameters in the greenhouse and evaluates the quality of the product. References 10, figures 3